PREDICTIVE MAPPING OF CRITICAL LAND IN BENGAWAN SOLO WATERSHED: AN INTEGRATED APPROACH USING LANDSAT IMAGERY AND TERRAIN ANALYSIS - Simarmata, Nirmawana; Sari, Dewi Nawang; Fathya, Annisha Bunga; Harta, M Sri (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2024)
Inappropriate land use can have negative impacts, increasing the risk of land becoming critical. Managing critical land and growing human needs is essential to balance land and water resources. This research aims to map necessary land in the Bengawan Solo watershed. The research method integrates remote sensing and geographic information system (GIS) methods. Critical land analysis was conducted based on the Regulation of the Director General of Watershed and Protected Forest Control Number P.3/PDASHL/SET/KUM.1/7/2018, which is used as a reference in determining whether land is categorized as critical land. The regulation uses 4 (four) variables in its processing: land cover variables, slope, erosion hazard level, and forest area. The study results show land criticality in the Bengawan Solo watershed in 2023. Most areas have low slopes (0-8%), considered non-critical, covering 30.50% of the total area. In contrast, the Potentially Critical category (8-15%) dominates with 45.94% of the area, indicating potential risks in moderately steep areas. Areas with steeper slopes fall into the Critical (10.29%) and Very Critical (2.68%) categories.